Book Review: L. Giorgi, and A. Pearman (eds.) with A. Tandon , D. Tsamboulas and C. Reynaud Project and Policy Evaluation in Transport - Berechman, Joseph (European Journal of Transport and Infrastructure Research, 2004)
This book is a compilation of papers presented in a seminar on “Policy and project evaluation: context, theory and methods”, held in Brussels in 2000 and which was organized by the Interdisciplinary Center for Comparative Research in Social Sciences with support from the European Commission. In addition to the introductory chapter, written by two of the editors, the book contains 7 papers. These are roughly divided between 3 papers, which describe the “European scene”, and 4 papers, which review approaches and methods of transport evaluation. Needless to say, in a book of this nature some overlap between chapters is largely unavoidable. In general, however, I find the book to be well organized and the chapters quite informative and well written.